The Effect of Temperature on Filtration Loss and Mud Cake on The Concentration of Corn Starch Using the KCl-Polymer Sludge System - Safira Azzahra fira; Lestari; Lisa Samura; Asri Nugrahanti; Rachmi Kartini (Penerbitan Universitas Trisakti, 2023)
Drilling mud is a type of fluid that can help smoothing a drilling. The function of the drilling mud in the drilling process is to lift the drilling cutting. In this laboratory research, corn starch was used as a substitute for starch to reduce filtration loss. Corn starch is made by cleaning, drying, grinding, and sieving. The purpose of this research is to make mud with the addition of corn starch. its effect on filtration loss and mud cake at two temperature conditions. In this study the use of corn starch to be mixed into the mud with concentrations of 3 grams, 5 grams, 7 grams, 9 grams, and 11 grams. Accordingly, it can be seen which mud composition complies with the standard drilling mud specifications. Laboratory test results showed that the addition of corn starch additives caused a decrease in filtration loss for each difference in concentration and temperature. With the addition of 11 grams of corn starch, filtration loss decreased from 6.2 ml to 4.4 ml at 80°F, and it decreased from 5.2 ml to 3.9 ml at 200°F. In addition, corn starch additives cause the thickness of the mud cake formed to decrease. At a temperature of 80 oF the thickness of the mud cake decreased from 0.76 mm to 0.46 mm, while at a temperature of 200 oF it decreased from 0.62 to 0.42 mm. Based on the research results, corn starch additives and temperature influence changes in filtration loss and mud cake.